Psikoedukasi Berbasis Video dan Diskusi Kelompok dalam Meningkatkan Pengetahuan Motivasi Belajar - Dawamah, Siti Muzaro’atut; Djudiyah, Djudiyah (Continuous Education: Journal of Science and Research, 2025)
Learning motivation is an important psychological factor that plays a role in determining students academic success. Adequate motivation encourages students to actively engage in the learning process, while low motivation can hinder the achievement of learning goals. Low student learning motivation is often influenced by a lack of self-awareness, weak environmental support, and a minimal understanding of the goals and benefits of learning. Therefore, appropriate intervention efforts are needed to improve students' knowledge regarding learning motivation. This study aims to determine the effectiveness of video-based psychoeducation and group discussions in improving students knowledge of learning motivation. The study used a pre-experimental design with a one-group pretest–posttest model. The study subjects consisted of 33 students of Madrasah Tsanawiyah (MTs) in Malang City. The research instrument was a questionnaire on learning motivation knowledge administered before and after the intervention. Data were analyzed using a paired sample t-test to determine differences in pre-test and post-test scores. The analysis results showed a very significant difference between students' knowledge of learning motivation before and after the intervention (t = -8.970; p < 0.001). The average post-test score (mean = 7.12) was higher than the pre-test score (mean = 4.45). Furthermore, the effect size was very large (Cohens d = 1.56), indicating a strong intervention effect. These findings indicate that video-based psychoeducation and group discussions are effective in improving MTs students learning motivation and knowledge.